The utility of the Sydney Melancholia Prototype Index (SMPI) for predicting response to electroconvulsive therapy in depression: A CARE Network study. (November 2022) - Waite, S.; Tor, P.C.; Mohan, T.; Davidson, D.; Hussain, S.; Dong, V.; Loo, C.K.; Martin, D.M.
Abstract: An enhanced understanding of clinical predictors of positive ECT outcome could assist with the decision to prescribe ECT for select patients. Reliable predictors of ECT response such as psychotic symptoms and age have been identified, however, studies of melancholia and ECT response have been inconsistent. The Sydney Melancholia Prototype Index (SMPI) is a clinical measure designed to differentiate melancholic and non-melancholic depression. This study aimed to investigate whether melancholic depression (as measured by the clinician rated version of the SMPI) predicted a better response to ECT than non-melancholic depression. The study included data collated from four participating sites in the Clinical Alliance for ECT and Related treatments (CARE) network. The primary outcome was response (>50% improvement) on the Montgomery Asberg Depression Rating Scale (MADRS) and the secondary outcome was raw change in MADRS score. Of the 329 depressed patients included in the study, 81% had melancholic features and 76% met criteria for clinical response. SMPI defined melancholia was associated with older age, higher pre-treatment mood scores and presence of psychosis. Melancholia as defined by the SMPI, however, did not significantly predict either clinical response or overall mood improvement with ECT in multivariate analyses. Instead, older age, greater pre-treatment depression severity and the use of bifrontal compared to right unilateral ultrabrief ECT were significant predictors of mood improvement. Path analysis showed that higher pre-treatment mood score and older age were independently associated with mood improvement with ECT.